New information and communication technologies in development professional competence of teachers of high level of the province Pasco - Valentín-Melgarejo, Teófilo F. (2019)
The fundamental purpose of the new technologies of information and communication in the development of professional competition of the educational one, are to guide and to toast to the educational ones on the importance of the technology of information and communication with the purpose that allows to improve their classroom practices, to create environments of more dynamic and more interactive learnings to supplement the teaching process and their students' learning, to facilitate the work in team and the cultivation of social attitudes with the learning community. Also, to improve their development in their professional acting and this way, enriching the pedagogic practices using the new technology of information and communication, stimulating this way the mental processes, making more significant the teaching act - learning when allowing their students to understand that the technology is applicable to all the areas of the knowledge and not specifically to a, achieving that this is an actor in the construction of its own learning. To be able to obtain better results during the pedagogic practices, the educational one should be competent in their professional acting so that this way it achieves better results in their students, of chord with the new technological advances.